The knowledge, attitudes and behaviors of hospital nurses on smoking cessation interventions: a cross-sectional study - Marta Čivljak; Lovro Ačkar; Livia Puljak (BMC, 2023)
Abstract Background Smoking is a major public health problem in Croatia. It is unknown to what extent nurses in Croatia use interventions for smoking cessation to help their patients. This study aimed to analyze the knowledge, attitudes and behaviors of hospital nurses on smoking cessation interventions. Methods We conducted a cross-sectional study in Zagreb, Croatia, in 2022 on a convenient sample of hospital nurses. We collected data with a questionnaire that included sociodemographic questions and questions about the frequency of implementation of 5 A's (Ask, Advise, Assess, Assist, Arrange) interventions for smoking cessation during their work using the Helping Smokers Quit (HSQ) survey, participants' attitudes and knowledge about smoking cessation skills and the smoking status of the nurses. Results There were 824 nurses employed in the targeted departments; 258 nurses participated in the study (response rate: 31%). Among them, 43% responded that they always ask patients about their use of tobacco products. Only 2.7% indicated that they always help the patient to stop smoking. Very few (2%) attended any training in the past two years about helping patients to quit smoking, and 82% never had such training. 44% of the included nurses were smokers. Nurses who smoked stated more frequently than nonsmokers they should not be role models for their patients by avoiding smoking (P 0.001). Additionally, patients were less frequently questioned about their inability to stop smoking by nurses who smoked than nurses who did not smoke (P = 0.010). Conclusion Even though smoking cessation interventions delivered by nurses were proven effective, such interventions are used by a small number of surveyed nurses. A small number of nurses have received training to help them support smokers in quitting. The high smoking prevalence among nurses may impact their attitudes and the implementation of workplace smoking cessation efforts.